EFFECTS OF VITAMIN C IN HIGH-ENERGY FEEDS ON GROWTH AND SURVIVAL RATE OF TIGER GROUPER SEEDS (Epinephelus fuscoguttatus) - Pinandoyo, Pinandoyo; Hutabarat, Johannes; Nugroho, Ristiawan Agung; Herawati, Vivi Endar (Aqusains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2017)
This research was aimed to study the effect of vitamin C on diets with low protein and high energy content on growth and survival rate of tiger grouper (Epinephelus fuscoguttatus) juveniles. It is also to know the dose or the best level concentration of vitamin C on growth and survival rate of tiger grouper (E. fuscoguttatus) juveniles. Tiger Grouper juveniles of 0,77+0,07 g initial body weight were reared in aquarium 60 cm x 40 cm x 40 cm with 7 ind. / 35 L. Artificial feed were fed in at satiation. The juveniles were fed dry pellet diets which containing 40% protein and 20% lipid in different levels of vitamin C (Ascorbate-2-Sulfate):0 mg/kg, 75 mg/kg, 150 mg/kg, 225 mg/kg. The experimental laboratoris method was conducted using Completely Randomized Design with three replicate for each treatment. The result of the experiment showed that there was a very significant effect of treatments on the SGR (Spesific Growth Rate), FCR (Feed Conversion Ratio), PER (Protein Efficiency Ratio), SR (Survival Rate) of tiger grouper (E. fuscoguttatus) juveniles (P < 0,01). That values more higher after added vitamin C (Ascorbate-2-Sulfate). Best treatment was obtained at supplementation vitamin C of 150 mg/kg. On the other hand be lower at highest dose on treatment D (225 mg/kg). Its indicated that vitamin C can improve and give better on growth and survival rate. The optimum condition of water quality also have been led to significant improvement in growth and survival rate